Predicting reaction barriers of hydrogen atom transfer in proteins [data] - Riedmiller, Kai; Reiser, Patrick; Bobkova, Elizaveta; Maltsev, Kiril; Gryn’ova, Ganna; Friederich, Pascal; Gräter, Frauke (Universität, 2023)
Hydrogen atom transfer (HAT) reactions are important in many biological systems. As these reactions are hard to observe experimentally, it is of hi...